Violence and migration: Evidence from Mexico's drug war - Sukanya Basu; Sarah Pearlman (IZA Journal of Development and Migration, 2017)
The effect of violence on people's residential choice remains a debated topic in the literature on crime and conflict. We examine the case of the drug war in Mexico, which dramatically increased the number of homicides since late 2006. Using data from the Mexican Census and labor force surveys, we estimate the impact of violence on migration at the municipal and state levels. To account for the endogeneity of violence, we use kilometers of federal highways interacted with cocaine supply shocks from Colombia as an instrument for the annual homicide rate. We argue that highways are good measures of pre-existing drug distribution networks, and the interaction with supply shocks arising in Colombia captures the time-variant nature of the value of these routes. After controlling for observed and unobserved area level heterogeneity, we find little evidence that increases in homicides have led to out-migration, at the domestic level. We also find little evidence of international migration at the municipal level, but some evidence of it at the state level. Our results show a muted migration response that is incompatible with a story of wide-scale displacement from the violence.
Keywords: O12; K42; O54; J11; 330; Homicides; Migration; Drug distribution networks; Mexico; Conflict